Ellen Foster : a novel - Gibbons, Kaye, 1960- (Algonquin Books of Chapel Hill, 2012)
Having suffered abuse and misfortune for much of her life, a young child searches for a better life and finally gets a break in the home of a loving woman with several foster children
Keywords: alkoholici; děti; dívky; pěstouni; alcoholics; children; girls; foster parents; Spojené státy americké (jižní oblast); United States, Southern; americké novely; American novellas